Comparison of cost and rubber production at flat and hilly area: case study in FGV Laka Selatan 02 / Muhammad Hafizi Ibrahim - Ibrahim, Muhammad Hafizi (Faculty of Plantation and Agrotechnology, 2018)
Topography is the main element that gives effect to the productivity of rubber. The aim of the study is to identify different of latex (rubber) production and cost of rubber production in flat and hilly areas. The study was conducted at Felda Global Venture Laka Selatan 02 where there is a region (07F) that has two differences topography that are flat and hilly. The study used secondary data which information of rubber yield and cost productions were collected from the database of the company. The rainfall data was used as a reference in this study. The data was collected from January 2016 until December 2017 and was analysed using independent t-Test. From the result, it shows that average production of latex (rubber) in flat area was higher than hilly area by using 24 months of the data. Meanwhile, the result shows that cost of rubber production at flat area is higher than hilly area caused by the high latex (rubber) production at the flat area. Different in the productivity was affected by the several factors such as nutrient and water availability. Both of the elements are the basic need for each crop to growth and producing yield.